Norovirus trends in British Columbia from 2021 to 2022: the relationship between wastewater surveillance and clinical outbreak data during the COVID-19 pandemic - Samantha Treagus; Jennifer Kopetzky; Christine Tchao; Tracy Chan; Farida Bishay; Hyo Jin Jeong; Daisy Yu; Angela Kong; Sarah C. Mansour; Natalie Prystajecky (Scientific Reports)
Abstract Norovirus causes frequent global outbreaks and significant financial and operational burdens on healthcare systems. Albeit, norovirus is a non-notifiable disease in many jurisdictions. Surveillance is focused on community outbreaks rather than routine monitoring, making assessment of community transmission difficult. Wastewater based epidemiology (WBE) can identify disease surges and confirm circulation of new variants of SARS-CoV-2, and could be applied to norovirus. This study sought to identify appropriate normalization techniques for norovirus in wastewater, evaluate the relationship between wastewater and outbreak data, and assess norovirus trends in 2021 and 2022 in British Columbia, Canada. A total of 1093 influent wastewater samples, from five municipal wastewater plants, were collected between January 2021 and November 2022. Samples were tested using qRT-PCR for norovirus genogroups I and II. Clinical outbreak data from 2021 to 2022 were significantly correlated to normalized norovirus levels in wastewater. During the first six months of 2022, the number of norovirus outbreaks and the concentrations of norovirus in wastewater were significantly higher than the same timeframe in 2021 (p = 0.016 and p < 0.0001 respectively). Easing COVID-19 countermeasures in 2022 may explain higher norovirus levels and outbreaks that year. WBE is useful for monitoring norovirus within the community and addresses gaps in clinical disease reporting.